2015
DOI: 10.1177/0022034515592593
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Level of Circulating Platelet-derived Microparticles in Oral Cancer

Abstract: Numerous studies have demonstrated that circulating microparticles (MPs) play important roles in a variety of diseases (e.g., atherosclerosis, hypertension, and diabetes), but the association between circulating MPs and oral squamous cell carcinoma (OSCC) remains largely unknown. In the present study, the circulating platelet-derived MPs (PMPs) in 63 patients with OSCC, 22 patients with infected keratocystic odontogenic tumor, and 31 healthy volunteers were characterized and quantified by flow cytometric analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
0
47
0
2
Order By: Relevance
“…Our previous study demonstrated that elevated levels of circulating MPs were closely correlated with the secretion of inflammation-related cytokines and so might be a cause of increased procoagulant activity in patients with OSCC (Ren et al 2016). However, the changes in different phenotypes of circulating MPs in OSCC are still to be clarified.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study demonstrated that elevated levels of circulating MPs were closely correlated with the secretion of inflammation-related cytokines and so might be a cause of increased procoagulant activity in patients with OSCC (Ren et al 2016). However, the changes in different phenotypes of circulating MPs in OSCC are still to be clarified.…”
Section: Discussionmentioning
confidence: 98%
“…Circulating MPs were isolated and detected according to our previous study (Ren et al 2016). Briefly, 5 mL of venous citrated blood was collected and centrifuged at 1,550 g for 20 min.…”
Section: Isolation and Flow Cytofluorometric Analysis Of Circulating Mpsmentioning
confidence: 99%
“…Raised levels of circulating pMVs have been detected in young women with polycystic ovary syndrome (Willis et al, 2014), in patients with rheumatoid arthritis in which pMVs express CLEC-2 (Gitz et al, 2014) and in patients with antiphospholipid antibodies in which pMVs correlate with anti-β2-GP (Chaturvedi et al, 2015). Additionally, elevated levels of circulating pMVs contribute to the increase PCA in patients with oral cancer (Ren et al, 2015). …”
Section: Platelet-derived Microvesicles and Cardiovascular Diseasementioning
confidence: 99%
“…MP were isolated from peripheral venous blood (circulating MP) or lesional fluid from VM patients (lesional MP) as similar to our previous studies (Ren et al , ,b). Briefly, venous blood (5 ml) was collected on citrated tubes from VM patients or healthy volunteers while lesional fluid was drawn from VM patients.…”
Section: Methodsmentioning
confidence: 99%